Both CRF1 and CRF2 receptors in the bed nucleus of stria terminalis are involved in baroreflex impairment evoked by chronic stress in rats - Oliveira, Leandro A. [UNESP] (2021)
Chronic exposure to adverse events has been proposed as a prominent factor involved in etiology and progression of cardiovascular dysfunctions in humans and animals. However, the neurobiological mechanisms involved are still poorly understood. In this sense, chronic stress has been reported to evoke neuroplasticity in corticotropin-releasing factor (CRF) neurotransmission in several limbic structures, including the bed nucleus of the stria terminalis. However, a possible involvement of BNST CRF neurotransmission in cardiovascular dysfunctions evoked by chronic stress has never been reported. Thus, this study investigated the involvement of CRF1 and CRF2 receptors within the BNST in cardiovascular changes evoked by chronic stress in rats. We identified that exposure to a 10-day chronic variable stress (CVS) protocol decreased expression of both CRF1 and CRF2 receptors within the BNST. These effects were followed by increased arterial pressure and impairment of baroreflex function, but without changes on heart rate. Bilateral microinjection of either the selective CRF1 receptor antagonist CP376395 or the selective CRF2 receptor antagonist antisauvagine-30 into the BNST did not affect CVS-evoked arterial pressure increase. Nevertheless, BNST treatment with CP376395 decreased both tachycardic and bradycardic responses of the baroreflex in non-stressed rats; but these effects were not identified in chronically stressed animals. BNST pharmacological treatment with antisauvagine-30 decreased the reflex tachycardia in control animals, whereas reflex bradycardic response was increased in CVS animals. Altogether, the results reported in the present study indicate that down regulation of both CRF1 and CRF2 receptors within the BNST is involved in baroreflex impairment evoked by chronic stress.